Formulation strategy to reach a balance among dietary essential amino acids for Nile tilapia juveniles - Romaneli, Rafael de Souza; da Silva, Maria Fernanda Oliveira; Masagounder, Karthik; Fernandes, João Batista Kochenborger [UNESP]; Fracalossi, Débora Machado (FapUNIFESP (SciELO), 2024)
Diets with high protein levels but unbalanced amino acid (AA) profiles can lead to poor AA utilization, increasing nitrogenous compound excretion and feed costs. Our study aimed to develop a formulation strategy to maintain a balanced dietary AA profile with a low protein level for Nile tilapia juveniles without compromising growth. Fish (6.75 ± 0.07 g) were fed on one of four isoenergetic diets with varied protein concentrations and AA profiles twice daily to apparent satiation for 41 days. The trial included four dietary treatments containing either 321 (32HighLys and 32LowLys) or 292 and 222 g protein kg–1 (29BAL and 22BAL, respectively) with five replicates per diet, making a total of 20 experimental units in a completed randomized design. The growth of fish fed the 29BAL diet was not compromised; weight gain (WG) and thermal growth coefficients were similar to those fed the 32HighLys and 32LowLys diets. However, the protein gain of those fish fed the 32HighLys diet was significantly higher than that of those fed the other diets. The 22BAL diet promoted the lowest growth, and its higher protein-energy ratio led to increased body lipid content. Therefore, the formulation strategy to supply balanced dietary AA to Nile tilapia reduced digestible protein from 32 to 29 %, without compromising fish growth and allowing a 12 % decrease in the excretion of nitrogenous waste.
Keywords: environmentally friendly diets; nitrogen excretion; protein quality